Pregnancy, childbirth, and breastfeeding experience of women with epilepsy in Me’enit community, South West Ethiopia - Rahel Yaekob; Tefera Belachew (BMC Pregnancy and Childbirth)
Abstract Introduction Poor obstetric care leading to prenatal brain injury is thought to be one potential cause of epilepsy. Epilepsy affects approximately 0.5–1.0% of women of childbearing age. In the Me’enit community, due to poor delivery practices (delivering in a standing position) and suffering from birth trauma, there are many women with epilepsy. Thus, this study aimed to explore the pregnancy, childbirth, and breastfeeding experiences of women living with epilepsy in the Me’enit community, in southwest Ethiopia. Methods A phenomenological approach was employed to gather data on women with epilepsy (WWE) on their pregnancy, childbirth, and breastfeeding experiences. The study participants were women with epilepsy in the reproductive age group (15–49 years) in the selected areas. Data were collected from participants through in-depth interviews with 15 women with epilepsy who experienced childbirth. The rigor and trustworthiness of the study were maintained based on Lincoln and Guba’s criteria of credibility, dependability, conformability, and transferability. The data were analyzed by using ATLAS. ti 7.1.4. software and organized into thematic categories. Verbatim the transcripts were used as illustrations to uncover the meaning of the participants’ experiences. Results The pregnancy, childbirth, and breastfeeding experiences of women with epilepsy were clustered into five theme clusters, including prepregnancy and childbirth practices, social stigma and support, institutional care, and support, seizure as a cause of maternal death, pregnancy as a cause of the seizure, and perception of feeding breast milk. The results show that there is no preconception care for WWE. There is also a knowledge gap and misconception about epilepsy by the family and surrounding community which resulted in stigma and discrimination against epileptic women. The discrimination started right from childhood as soon as they manifested the diseases. Maternal mortality in women with epilepsy was considered to be high. However, it was noted that epilepsy was not aggravated by the pregnancy and women with epilepsy breastfeed their children similarly to their non-epileptic peers. Conclusion The findings imply the need for special attention to WWE before, during, and after pregnancy to improve maternal and child health. Behavioral change communication needs to target the knowledge gap and misconception about epilepsy by the family and surrounding community to reduce stigma and discrimination against epileptic women and associated maternal mortality.